Behind Japanese Lines : An American Guerrilla in the Philippines - Hunt, Ray C., 1919- (Book collections on Project MUSE., 2014)
Behind Japanese Lines has a great deal to say about the relations with the Filipinos and about the problems of dealing with and fighting the Hukbalahaps, the communist guerrillas or, indeed, in opposing the Japanese. This book adds considerable insights into the significance of guerrilla warfare as it relates to modern warfare in general.